The Impact of Teachers Work Motivation on Their Instructional Performance at SD Integral Luqman Al Hakim - A. Ansorullah; Daud Ridwan, Daud Ridwan; Siti Qomariatul Munawaroh; Benny Prasetya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to examine the effect of Work Motivation on teachers’ Teaching Performance at SD Integral Luqman Al Hakim Bondowoso. A quantitative approach was employed, utilizing a simple linear regression design. The study involved a total of 42 teachers as research respondents. Data analysis was conducted using SPSS version 25, encompassing prerequisite assumption tests (normality and linearity) followed by hypothesis testing. The results of the normality test indicated that the data satisfied the assumption of normal distribution, thereby allowing the regression analysis to be performed appropriately. The ANOVA results demonstrated that the regression model was statistically significant (p < 0.05), indicating a meaningful effect of Work Motivation on Teaching Performance. The correlation coefficient (R) of 0.759 reflects a strong and positive relationship between the variables, while the coefficient of determination (R²) of 0.576 suggests that 57.6% of the variance in Teaching Performance can be explained by Work Motivation, with the remaining variance attributable to other factors beyond the scope of the research model.